Experimental Examination of Steel Bar Reinforcements on the Compressive Responses of Square CFST Short Columns - Ayce Cathen, Winti; Abdul Azim, Abdullah; Abdul Razak, Abdul Karim; Ahmad Kueh, Beng Hong (IOP Publishing Ltd, 2026)
Square concrete-filled steel tube (CFST) columns offer construction efficiency but are significantly more prone to local buckling and possess lower confinement compared to circular sections. While various strengthening schemes exist, they often pose fabrication challenges or compromise steel tube integrity. This study investigates the mechanical behaviour of square CFST short columns reinforced with internal steel bars attached via a spot-welding technique, designed to minimize residual stress and simplify fabrication. Five specimens were tested under axial compression to evaluate the effects of varying steel bar diameters (10 mm and 12 mm) and quantities (4, 8 or 12 bars). The configuration used in this study also differs from those in previous studies. Experimental results indicate that the reinforced specimens achieved ultimate axial loads ranging from 559.4 kN to 839.2 kN, representing a significant capacity increase of 47% to 121% over the unreinforced specimen. Furthermore, the spot-welded reinforcement enhanced ductility by up to 103% and total energy absorption by up to 217%. The findings conclude that this spot-welded internal reinforcement method is an effective, construction-friendly solution for delaying local buckling and improving the overall compressive performance of square CFST columns.